The prospect of malaria elimination in the Arabian Peninsula: A population genetic approach - Al-Hamidhi, Salama; Mahdy, Mohammed A. K.; Idris, Mohamed Ahmed; Bin Dajem, Saad M.; Al-Sheikh, Adel Ali H.; Al-Qahtani, Ahmed; Al-Hashami, Zainab; Al-Farsi, Hissa; Al-Mekhlafi, Abdulsalam M.; Saif-Ali, Riyadh; Beja-Pereira, Albano; Babiker, Hamza A. (Elsevier, 2014)
Background In the Arabian Peninsula malaria control is progressing steadily, backed by adequate logistic and political support. As a result, transmission has been interrupted throughout the region, with exception of limited sites in Yemen and Saudi Arabia. Here we examined Plasmodium falciparum parasites in these sites to assess if the above success has limited diversity and gene flow. Methods We examined 108 P. falciparum isolates in three sites in Yemen (Taiz, Dhamar and Hodeidah) and 91 isolates from Saudi Arabia (Jazan). Nine microsatellites were analyzed for allelic diversity, multi-locus haplotype and inter-population differentiation. Results Diversity at each locus (unbiased heterozygosity [H]) was relatively lower in Yemen; (Hodeidah, H = 0.615, Taiz, H = 0.66, Dhamar, H = 0.481), compared to Saudi Arabia (Jazan, H = 0.76). Microsatellites were distributed widely and private alleles, detected in a single population, were rare. Pairwise comparisons revealed that parasites population in Dhamar was relatively distanced (FST = 0.19). However, Taiz (Yemen) (FST = 0.065) and Hodeidah (FST = 0.107) populations were closer to that in Jazan (Saudi Arabia). Nonetheless, parasites in the four sites can be considered as one population. Conclusion Although malaria risk in Saudi Arabia has been cut considerably, the extent of diversity and parasite genetic structure are indicative of a large population size. Elimination strategy should target demographic factors that favor parasite dispersal and flow of imported malaria.